Disparitas Putusan Hakim Terhadap Denda Tindak Pidana Korupsi Di Pengadilan Tindak Pidana Korupsi Pada Pengadilan Negeri Pekanbaru - Debora Aprissa Hutagaol; Mexsasai Indra; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The scale of corruption continues to increase, corrupt behavior has become entrenched and institutionalized. The three sectors most vulnerable to corruption are political parties, police and courts. The country suffered trillions of rupiah in losses due to this crime. While the cases handled were quite a lot, but still not able to recover state losses. The main cause is due to the comparison of the amount of fines that must be paid by the convicted person with the amount of state losses very far. So that the same demand for fines is currently not a solution for returning state losses. This is what causes the difficulty in dealing with corruption. With the current corruption law, which does not provide strict and narrow boundaries and standards, so the possibility is wide open for judges to use their discretion widely in determining the amount of fines in decisions that automatically cause disparities (differences) in decisions for similar cases, considering the large number of judges of corruption in Indonesia. Disparity in decisions often gives rise to diverse interpretations in people's lives and to the meaning of justice.The purpose of this thesis, namely: First, to find out the reason for the disparity in the fine of corruption in the Corruption Court at the Pekanbaru District Court, Secondly, to find out the ideal idea of the fine regulation of corruption to prevent disparity in decisions.This type of research is normative juridical research or can be referred to as doctrinal legal research. The technique of collecting data in this study is library research. From the results of the problem research there are two main things that are concluded, First, the reason for the disparity in the fine of corruption is the law on corruption or in court practice that currently does not have a narrow or clear benchmark or guideline (maximum limit) and the minimum is not far away), and comes from the judge (mindset and discretion) both internally and externally in making a decision (fine), Second, the ideal idea of the regulation of fine for corruption to prevent disparity in decisions is to reform the act law old corruption cases where the new one lists the amount of fines that must be decided by the judge in accordance with the amount of state losses due to the criminal acts of corruption committed.Keywords: Disparity of Judgment - Fines - Corruption Crimes